The effect of educational attainment and other socioeconomic factors on corruption participation - Alonte, Jennus J. (School of Economics, University of the Philippines Diliman, 2019)
This paper aims to study the effects of various socioeconomic factors, focusing on the relation of a person's highest educational attainment with their propensity to bribe, and the amount of which they give to access certain government service using clustered and detailed specifications for the education levels. The study intends to aid policymakers in making decisions regarding the importance of education as a deterrent to crime occurrences, in the hope to append to the Universal Access to Quality Tertiary Education Act of 2017 and add Primary and Secondary Education to the scope of the law. A test with specific groups of highest educational attainment on cross-sectional data from the Annual Poverty Index Survey 2017 reveal that, in the country, elementary undergraduates tend to bribe more than those with higher levels of education at 5 percent level with 0.667 log odds for the logit regression model. Elementary undergraduate's bribe decreases by 102.9 percent while high school undergraduates' amount of bribe decreases by 110.9 percent, showing that higher levels of education decreases bribery. Multiple regressions also produced significance in the regional effects, being married, income deciles and other wealth measurements. Findings are robust and consistent with the different econometric specifications used in the study -- ordinary least squares model, logit and probit estimations and a Heckman Two-Step Selection Model. We recommend more corruption studies, focused on bribery using more nationwide survey on access to government services to provide ancillary guidance for our policy-makers.